Plasma membrane transporters GAT-1 and GAT-3 contribute to heterogeneity of GABAergic synapses in neocortex - Melone, Marcello; Ciappelloni, Silvia; Conti, Fiorenzo (Frontiers in Neuroanatomy, 2014)
Cortical GABAergic synapses exhibit a high degree of molecular, anatomical and functional heterogeneity of their neurons of origins, presynaptic mechanisms, receptors, and scaffolding proteins. GABA transporters (GATs) have an important role in regulating GABA levels; among them, GAT-1 and GAT-3 play a prominent role in modulating tonic and phasic GABAAR-mediated inhibition. We asked whether GAT-1 and GAT-3 contribute to generating heterogeneity by studying their ultrastructural localization at cortical symmetric synapses using pre- and post-embedding electron microcopy. GAT-1 and GAT-3 staining at symmetric synapses showed that in some cases the transporters were localized exclusively over axon terminals; in others they were in both axon terminals and perisynaptic astrocytic processes; and in some others GAT-1 and GAT-3 were in perisynaptic astrocytic processes only. Moreover, we showed that the organizational pattern of GAT-1, but not of GAT-3, exhibits a certain degree of specificity related to the post-synaptic target of GABAergic synapses. These findings show that symmetric synapses expressing GAT-1 or GAT-3 are heterogeneous, and indicate that plasma membrane transporters can contribute to synaptic heterogeneity.